The beautiful game - Méndez, Yamile Saied (Algonquin Young Readers, Workman Publishing, 2024)
"At thirteen years old, Valeria 'Magic' Salomón is already the best soccer player her town has ever seen. She has talent in spades and an abuelo whose tough-love coaching and lessons about 'strength and honor' have made her the star of the Overlords, the top boys' team in the state. But everything changes at the State Cup semi-final when Valeria gets her first period while Wearing. White. Shorts. After her team is unexpectedly eliminated, she goes from their secret weapon to their scapegoat. Soon, she doesn't have a team at all anymore. She's not sure she has a relationship with her grandfather either. Valeria's a fighter, however. And with the help of her grandmother and support of her cheerleader BFF, she finds herself on a girls' team for the first time. But the Amazons aren't exactly excited to have her there. After all, Valeria's spent years ignoring their existence. With the next tournament looming on the horizon, Valeria has a month to figure out her place on her new team and learn how to play like a girl." --